Effect of different protocols for estrus synchronization on reproductive performance of Santa Inês ewes under Amazon environmental conditions - Regina Oliveira da Silva; Roseane Pinto Martins de Oliveira; André Ferreira Silva; Franklyn Ferreira de Oliveira; João Paulo Ferreira Rufino; Márcia Lorena Monteiro da Silva (Acta Scientiarum. Animal Sciences, 2020)
The objective of this study was to evaluate the effect of different hormonal protocols on the reproductive performance of Santa Inês ewes in Amazon environmental conditions. Twenty-two Santa Inês ewes between 3 and 4 years-old were distributed in a randomized block experimental design, where the treatments consisted of two protocols for estrus synchronization (short and long) with eleven animals each. Data on the occurrence of estrus were described for each protocol. Data of estrus, pregnancy, and prolificity were firstly subjected to ANOVA and a subsequent Tukey’s test. Results were considered significant at p ≤ 0.05. The short-term protocol presented an interesting successful rate, where above 70% ewes tested had estrus. The long-term protocol also achieved a high successful rate, where above 80% ewes tested had estrus. However, comparing the protocols, the long-term protocol presented better results of positive estrus and pregnancy rates in ewes. Thus, it can be concluded that both protocols presented satisfactory results regarding estrus manifestation, and prolificity (lambs produced per ewe). However, under Amazon environmental conditions, the long-term protocol presented better results regarding positive manifestation of estrus and pregnancy rate.